Dip-Coating Self-Assembly Fabrication and Polarization Sensitive Photoresponse of Aligned Single-Walled Carbon Nanotube Film - Zhang, Jiazhen; Yang, Luhan; Xu, Huang; Zhou, Jie; Sang, Yuxiang; Cui, Zhuangzhuang; Liu, Changlong; Liu, Jingjing; Guo, Tianle; Wang, Xingjun; Wang, Lin; Chen, Gang; et al. (Sensors (Basel, Switzerland), 2022)
It is challenging to obtain wafer-scaled aligned films for completely exploiting the promising properties of semiconducting single-walled carbon nanotubes (s-SWCNTs). Aligned s-SWCNTs with a large area can be obtained by combining water evaporation and slow withdrawal-induced self-assembly in a dip-coating process. Moreover, the tunability of deposition morphology parameters such as stripe width and spacing is examined. The polarized Raman results show that s-SWCNTs can be aligned in ±8.6°. The derived two terminal photodetector shows both a high negative responsivity of 41 A/W at 520 nm and high polarization sensitivity. Our results indicate that aligned films with a large area may be useful to electronics- and optoelectronics-related applications.